Dietary isoflavones, urinary isoflavonoids, and risk of ischemic stroke in women(1)(2)(3) - Yu, Danxia (Am J Clin Nutr, 2015)
Background: Hormone therapy has been shown to increase risk of ischemic stroke in women. Plant-derived estrogens, particularly soy isoflavones, are known to have some estrogenic effects and have been marketed as natural alternatives to hormone therapy. Concerns have been raised about whether high isoflavone exposure may be related to ischemic stroke risk as well. Objective: We examined the dietary intake of isoflavones and the urinary excretion of isoflavonoids in relation to risk of ischemic stroke in women. Design: A prospective cohort study was conducted in 66,832 Chinese women (aged 40–70 y) who had no cardiovascular disease or cancer at baseline. Usual dietary intakes were assessed via in-person interviews with the use of a validated food-frequency questionnaire. Incident strokes were ascertained during follow-up home visits and confirmed by medical records. We also conducted a nested case-control study in postmenopausal women who had never used hormone therapy, including 1422 incident ischemic stroke cases and 1422 controls individually matched by age, date and time of urine sample collection, time since last meal, and use of antibiotics. Urinary isoflavonoids were measured with the use of high-performance liquid chromatography coupled with mass spectrometry. Results: During a mean follow-up of 10 y, 3110 incident ischemic strokes were verified. Dietary isoflavone intake was associated with increased risk of ischemic stroke; multivariable-adjusted HRs from lowest to highest quintiles were 1.00, 1.05, 1.10, 1.11, and 1.24, respectively (95% CI: 1.08, 1.42; P-trend = 0.002). In the case-control study, a similar positive association was observed for dietary isoflavones, but no significant associations were shown for the urinary isoflavonoid concentration [OR: 1.01 (95% CI: 0.77, 1.32) for comparison of extreme quintiles]. Conclusions: A habitually high intake of soy isoflavones may be associated with a modest but significant increase in risk of ischemic stroke in women. However, no association was shown for the urinary excretion of isoflavonoids.